Socio-Philosophical Aspects of Increasing the Political Activity of Youth in The Process of Modernization - Gaybullayeva Laylo Safarboyevna (Zien Journals, 2024)
The article describes the socio-philosophical aspects of increasing the political activity of young people in the process of modernization.
Keywords: neighborhood; youth; political activity; society